2021
DOI: 10.1016/j.jclepro.2021.126868
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment of urine, black and grey water separation for resource recovery in a new district compared to centralized wastewater resources recovery plant

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…For the sourceseparated brownwater treated at a decentralized alternative, the emissions were decreased in scenario DS1 but not in scenario DS2, which had high electricity consumption and consequently high overall emissions because of the Aurin treatment. According to Besson et al (2021), urine source separation has a low environmental footprint, with potential impacts on global warming decreased by 45% compared with centralized treatment. In the LCA performed by Spångberg et al (2014), a source separation scenario also performed well in terms of conserving energy and reducing GWP, but it increased the eutrophication and acidification impacts.…”
Section: Characterization Resultsmentioning
confidence: 99%
“…For the sourceseparated brownwater treated at a decentralized alternative, the emissions were decreased in scenario DS1 but not in scenario DS2, which had high electricity consumption and consequently high overall emissions because of the Aurin treatment. According to Besson et al (2021), urine source separation has a low environmental footprint, with potential impacts on global warming decreased by 45% compared with centralized treatment. In the LCA performed by Spångberg et al (2014), a source separation scenario also performed well in terms of conserving energy and reducing GWP, but it increased the eutrophication and acidification impacts.…”
Section: Characterization Resultsmentioning
confidence: 99%
“…This can also be a limiting factor in achieving circular nature-based systems, as the modern configuration of many urban areas still approaches water resources as one stream, when, in reality, several higher-purity (and -quality) streams exist, such as stormwater, greywater, blackwater, etc. [261,262]. For many of the NBS described, the input wastewater streams must have specific compositions; otherwise, the systems do not function appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…For many of the NBS described, the input wastewater streams must have specific compositions; otherwise, the systems do not function appropriately. At the same time, units such as urine-separating toilets require a separate drainage system to be implemented in order to separate streams, which requires investments in infrastructure [262]. This approach of separating waste/resource streams at the source has been a recent one which has not been implemented in many cities.…”
Section: Discussionmentioning
confidence: 99%
“…Faced with these challenges, several studies have shown the potential of decentralized excreta source separation systems in Frontiers in Environmental Science frontiersin.org terms of environmental impacts and for agricultural valorization, compared to conventional sanitation systems (Vinnerås and Jönsson, 2001;Winker et al, 2009;Lam et al, 2015;Kjerstadius et al, 2017;Harder et al, 2019). Life-cycle analyses show a real environmental gain in the case of urine source separation systems where nitrogen is: 1) separated from wastewater and no longer treated biologically by nitrification/ denitrification; and 2) valorized in agriculture as fertilizer (Bisinella de Faria et al, 2015;Martin, 2020;Besson et al, 2021;Hilton et al, 2021). Greenhouse and field trials have also shown that the effectiveness of urine-based fertilizers is close to that of synthetic nitrogen fertilizers (Martin, 2020;Martin et al, 2020).…”
Section: Factors and Trajectorymentioning
confidence: 99%